Visualizing Harbours in the Classical World : Iconography and Representation Around the Mediterranean - Ugolini, Federico (Bloomsbury Publishing Plc, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Contents -- Illustrations -- Acknowledgements -- Abbreviations -- Map -- 1 Introduction -- Aim and scope -- Literary review -- A new study of the iconography of maritimere presentations -- A selection of portable and fixed objects with harbourre presentations -- The organization of this monograph -- 2 Alexandria, Rome, Leptis Magna and the Triumphal Imagery of Monumental Harbours -- Introduction -- Alexandria -- Portus -- Leptis Magna -- Aspects of monumentality in ancient harbours across the Mediterranean -- Monumentality as a source of inspiration and a programmatic model for triumphal imagery -- Conclusion -- 3 Harbours in Graeco-Roman Art: Symbolism and Identity across the Mediterranean -- Introduction -- Symbolic message: Case studies of Rome, Puteoli and Leptis Magna -- Ideological message: Representations of the imperial and mercantile classes -- Propagandistic message: Th e iconography of imperial authority -- Conclusion -- 4 Portraying Maritime Cityscapes: An Imperial Perspective -- Introduction -- Claudius and Nero: Monumental infrastructure -- Trajan's Column: Control over the water -- The Arch of Septimius Severus: Authority -- Military control over the Mediterranean Sea -- Conclusion -- 5 The Mercantile Class: Economic Growth and Influence during the Imperial Era -- Introduction -- Harbour mosaics as evidence of the economy and trade -- Controlling the sea, sailing the sea: A depiction of a peaceful Mediterranean -- Commercial messages behind harbour scenes -- Conclusion -- 6 A Postcard from the Ancient Mediterranean: Aspects of Euergetism and Paideia in Representations of Maritime Cities -- Introduction -- Public sphere: Representations of safety and security -- Private sphere: Representations of abundance and prosperity.